2013
DOI: 10.1021/jp407105v
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Reaction Mechanisms of Thiophenol Adsorption on Gold Studied by Surface-Enhanced Raman Spectroscopy

Abstract: Thiophenol is commonly used as a model system for surface-enhanced Raman scattering (SERS) of molecules due to the strong affinity of the −SH group toward noble metal surfaces. By performing time-, temperature-, and pH-dependent measurements of thiophenol adsorption on commercial nanostructured gold SERS substrates, we have observed both physisorption and chemisorption processes. These two distinct adsorption regimes were found dependent on the pH which controlled the ionization state of thiophenol in an aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 31 publications
(53 reference statements)
4
72
0
Order By: Relevance
“…The resulting SERS spectra of thiophenol are in agreement with the literature . In spite of its high affinity for Au surfaces and relatively high concentration, thiophenol could displace the adsorbed species only to a limited extent (< 20%), confirming the strong interactions between capping agents and the NPs, which determined their long‐term stability. However, we were not able to discriminate whether the different SERS enhancement came from different thiophenol concentration at the surface or from structural properties of the AuNPs.…”
Section: Resultssupporting
confidence: 87%
“…The resulting SERS spectra of thiophenol are in agreement with the literature . In spite of its high affinity for Au surfaces and relatively high concentration, thiophenol could displace the adsorbed species only to a limited extent (< 20%), confirming the strong interactions between capping agents and the NPs, which determined their long‐term stability. However, we were not able to discriminate whether the different SERS enhancement came from different thiophenol concentration at the surface or from structural properties of the AuNPs.…”
Section: Resultssupporting
confidence: 87%
“…More detailed analysis shows that there is a shoulder band partially covered by the 1417 cm −1 v s (COO − ) band. The shoulder band at 1403 cm −1 belongs to the surface-bonded COO − group whereas the stronger band at 1417 cm −1 is due to non-bonded COO − group in 4-MBA [7]. The intensity ratios of the 1403 cm −1 band to the 1417 cm −1 band change from 0.55, 0.46, to 0.43, with pH values change from 13, 10, to 7, respectively.…”
Section: Resultsmentioning
confidence: 92%
“…Applications using SERS as the research tool can be found in the fields of analytical chemistry, surface science, and biomedical studies [4][5][6][7][8][9]. Most of the SERS studies have been carried out with molecules adsorbed on the surfaces of transition metals [10][11][12][13], particularly Ag and Au.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, 7-9 Examining the SERS signal of these systems with respect to pH changes 3, 10-12 , electrochemical potential 10, 13 , and temperature 3 allows for the elucidation of the analyte-substrate interaction. Molecules adsorbed at surfaces have been used to evaluate the distance dependence of the SERS effect.…”
Section: Introductionmentioning
confidence: 99%